2009
DOI: 10.1002/ibd.20538
|View full text |Cite
|
Sign up to set email alerts
|

Observer variability in the histologic diagnosis of microscopic colitis

Abstract: Both interobserver and intraobserver agreement were good in distinguishing among the 6 diagnostic categories, and excellent in distinguishing between microscopic colitis and nonmicroscopic colitis diagnoses. The histologic criteria for microscopic colitis provide for consistent and reproducible interindividual and intraindividual diagnoses in the evaluation of colonic biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…However, the histological criteria for MC were established in 1989, and in a previous US study, the inter-and intraobserver agreements were very reliable for the diagnostic categories of MC [14]. A recent Danish study [15] demonstrated a very good interobserver agreement when discriminating MC from normal histology, although there seems to be difficulties differentiating subgroups of MC.…”
Section: Discussionmentioning
confidence: 97%
“…However, the histological criteria for MC were established in 1989, and in a previous US study, the inter-and intraobserver agreements were very reliable for the diagnostic categories of MC [14]. A recent Danish study [15] demonstrated a very good interobserver agreement when discriminating MC from normal histology, although there seems to be difficulties differentiating subgroups of MC.…”
Section: Discussionmentioning
confidence: 97%
“…(Fernandez-Banares et al, 1999; Fine et al, 2000; Shah et al, 2001; Olesen et al, 2004; Pardi, 2004; Limsui et al, 2009) It has been suggested that the prevalence of MC is underestimated and the true prevalence of this disease is increasing in humans. (Olesen et al, 2004; Limsui et al, 2009; Zippi et al, 2010; Yen and Pardi, 2011) The cause(s) is uncertain (Pardi et al, 2007) but it has been suggested that infectious agents or some drugs may trigger the problem. (Pardi et al, 2002; Olesen et al, 2004; Beaugerie and Pardi, 2005; Fernandez-Banares et al, 2007)…”
Section: Discussionmentioning
confidence: 99%
“…MC is a less commonly reported form of human inflammatory bowel disease (IBD). The two major forms of human IBD are lymphocytic colitis and collagenous colitis (Fernandez-Banares et al, 1999;Shah et al, 2001;Olesen et al, 2004;Pardi, 2004;Limsui et al, 2009). It has been suggested that the prevalence of MC is underestimated and the true prevalence of this disease is increasing in humans Limsui et al, 2009;Zippi et al, 2010;Yen and Pardi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Considering MC as a single group vs. colitis of other types, agreement was found to be very good ( k = 0.80–0.95). Intra‐observer agreement was also good for the 6 disease categories ( k = 0.75–0.79), and even better on differentiating MC from the rest of the biopsies ( k = 0.84–0.91) . In another study including H&E‐stained biopsies from 125 patients diagnosed with CC, LC, MCi, nonspecific colitis/IBD and normal biopsies, inter‐observer agreement among three pathologists with different degrees of experience was seen to be good ( k = 0.81–0.89) in distinguishing MC (CC, LC and MCi) from nonspecific colitis/IBD and normal biopsies.…”
Section: Statements and Recommendationsmentioning
confidence: 89%